The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40201-021-00647-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nutrients and health risks from exposure to some heavy metals through the consumption of the farmed common carp (CYPRINUS CARPIO)

Abstract: Common carp (Cyprinus carpio) is one of the most important cultured fish species in Poland. The aims of our study were to determine the concentration of essential minerals in the muscle tissue of carp obtained from a pond culture and to compare the content of these minerals with the physiological norms of nutrition for the Polish population, Recommended Dietary Allowances (RDA), and Estimated Average Requirements (EAR). The non-carcinogenic and carcinogenic risk by assessment of the Estimated target hazard quo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…In Elsagh's study, the concentration of chromium metal in carp from the Caspian Sea was reported to be higher than the level determined by international standards, which was contrary to the result obtained in the present study; this inconsistency may have been due to the higher pollution of the Caspian Sea and enormous increase in using pesticides in this area compared to water basins of Hamadan province (37). In a study by Tkachenko et al, the amount of chromium metal was determined to be higher than that of cobalt metal in farmed carp in Poland, which was in agreement with our study results (38). Salemi and Hosseini Alhashemi reported that the concentration of chromium in common carp from the shores of Dez was equal to 0.02 mg/kg dry weight and was lower than the limit defined by international standards, which was consistent with our study findings; however, they demonstrated that the concentration of nickel in this fish was equal to 1.41 mg/kg dry weight and was higher than the limit defined by international standards, which was inconsistent with the findings from this study (39).…”
Section: Resultssupporting
confidence: 93%
“…In Elsagh's study, the concentration of chromium metal in carp from the Caspian Sea was reported to be higher than the level determined by international standards, which was contrary to the result obtained in the present study; this inconsistency may have been due to the higher pollution of the Caspian Sea and enormous increase in using pesticides in this area compared to water basins of Hamadan province (37). In a study by Tkachenko et al, the amount of chromium metal was determined to be higher than that of cobalt metal in farmed carp in Poland, which was in agreement with our study results (38). Salemi and Hosseini Alhashemi reported that the concentration of chromium in common carp from the shores of Dez was equal to 0.02 mg/kg dry weight and was lower than the limit defined by international standards, which was consistent with our study findings; however, they demonstrated that the concentration of nickel in this fish was equal to 1.41 mg/kg dry weight and was higher than the limit defined by international standards, which was inconsistent with the findings from this study (39).…”
Section: Resultssupporting
confidence: 93%